Peran Strategis Standar Biaya Keluaran dalam Meningkatkan Penganggaran Berbasis Kinerja Kementerian Agama - Kusnadi, Endang (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper reviews the strategic role of Output Cost Standards in improving performance-based budgeting in the Ministry of Religious Affairs to improve the quality of budget planning. This study uses a qualitative method with a descriptive analysis approach regarding the motives for implementing the Inspectorate General's Output Cost Standards and the motives for refusing to implement the Output Cost Standards in other units. This study is expected to provide accurate information about trends in the motives for implementing SBK. Apart from that, the author also wants to dig deeper by analyzing the effectiveness of the use of SBK at the Inspectorate General to support the role of Output Cost Standards in improving Performance-Based Budgeting in their units for the reasons: (1) knowing the motives for implementing Output Cost Standards in preparing and reviewing performance-based budgets, (2) evaluate the achievement of outputs and outcomes as well as the efficiency of implementing Output Cost Standards, and (3) analyze motive factors and evaluate Output Cost Standards in improving the quality of performance-based budgeting. The aspects studied show the: motives for implementing Output Cost Standards, evaluation of the implementation of Output Cost Standards at the Inspectorate General, and the strategic role of Output Cost Standards in improving Performance-Based Budgeting.